Transposition of the great arteries: factors influencing prenatal diagnosis. (3rd March 2014) - Bertagna, F.; Rakza, T.; Vaksmann, G.; Ramdane‐Sebbane, N.; Devisme, L.; Storme, L.; Francart, C.; Vaast, P.; Houfflin‐Debarge, V.
ABSTRACT Objective The objective of this study is to highlight the factors that may affect prenatal diagnosis of transposition of the great arteries (TGA) in order to improve it. Methods This is a retrospective study performed between 2004 and 2009 in the maternity units from North of France. We identified a total of 68 cases of TGA (isolated or associated with only VSD or coarctation of aorta), of which 32 (47.1%) had prenatal diagnosis (PND+) and 36 did not (PND−). Maternal characteristics and ultrasound factors were studied in relation to PND. Results Maternal weight and body mass index were significantly higher in the PND− group (70.4 kg and 26.5 kg/m2 vs 63.6 kg and 23.6 kg/m2, respectively). Maternal obesity (body mass index >30) was significantly more frequent in the PND− group (27.8% vs 12.5%). More than a quarter of TGA (28.1%) were diagnosed during the third trimester. Conclusion Obesity is the main cause of missed PND of TGA. Obese patients with suboptimal prenatal scans may benefit from reassessment of fetal cardiac anatomy and/or from referral for fetal echocardiography. © 2014 John Wiley & Sons, Ltd.